2013
DOI: 10.1103/physreva.88.062710
|View full text |Cite
|
Sign up to set email alerts
|

Electron-impact-ionization dynamics of five C2to C4perfluorocarbons

Abstract: Reprinted with permission from the American Physical Society: Phys. Rev. A 88, 062710 c (2013) by the American Physical Society. Readers may view, browse, and/or download material for temporary copying purposes only, provided these uses are for noncommercial personal purposes. Except as provided by law, this material may not be further reproduced, distributed, transmitted, modied, adapted, performed, displayed, published, or sold in whole or part, without prior written permission from the American Physical Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 76 publications
3
17
0
Order By: Relevance
“…However, for a few fluorocarbons, the results obtained using such orbital parameters do not agree better with experimental data compared to Hartree Fock (HF) orbitals and overestimate experimental results. For C 2 F 6 , Gupta et al [34] have shown that the results obtained using the density functional theory (DFT) (ωB97X) functional for orbital binding and kinetic energies are in reasonable agreement with the P3-EPT calculations of Bull et al [14], with slight variations at the peak of the cross section. The results obtained using the DFT (ω B97X-D) functional are slightly higher than those obtained using the DFT (ωB97X) functional, which may be owing to the inclusion of dispersion in the functional.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…However, for a few fluorocarbons, the results obtained using such orbital parameters do not agree better with experimental data compared to Hartree Fock (HF) orbitals and overestimate experimental results. For C 2 F 6 , Gupta et al [34] have shown that the results obtained using the density functional theory (DFT) (ωB97X) functional for orbital binding and kinetic energies are in reasonable agreement with the P3-EPT calculations of Bull et al [14], with slight variations at the peak of the cross section. The results obtained using the DFT (ω B97X-D) functional are slightly higher than those obtained using the DFT (ωB97X) functional, which may be owing to the inclusion of dispersion in the functional.…”
Section: Resultsmentioning
confidence: 72%
“…Orbital energies are calculated at various levels of theoretical approximation using the Gaussian 09 [139] package. Bull et al [14] have recently suggested that the orbital parameters employed in the calculation of Q ion using the BEB method should be obtained using a high level of theoretical approximation. They have utilized the partial third-order electron propagator theory (P3-EPT) level of approximation for obtaining orbital parameters for binding energies less than 20 eV.…”
Section: Resultsmentioning
confidence: 99%
“…While a large number of electron ionization cross-sections have been reported for SF6, summarised in a number of reviews [2,7,8], there is varying agreement between the different determinations. This variation is due partly to the fact that conventional mass spectrometers and weak-field ion sources with small source apertures discriminate against ions formed with high kinetic energy [9,10]. It is now well-established that SF6, like other small saturated perfluorinated species, does not have a bound parent cation in the Franck-Condon window.…”
Section: Introductionmentioning
confidence: 99%
“…Gaining a detailed understanding of the microscopic dynamics of electron ionization for a 'large' molecular target like SF6 is a challenging task due to the array of possible ionized states that may be accessed [10,14]. Electron ionization is a collisional interaction, in which the electron may in principal transfer any fraction of its kinetic energy to the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…However, as this is not the only available process during the electron impact, the BEB model usually overestimates the ionization cross section [40,41].…”
Section: Total Ionization Cross Sectionsmentioning
confidence: 99%